The acceptability and feasibility of a virtual mantram program for patients with posttraumatic stress disorder and substance use disorders: mixed method results - Sean Ferkul; Zena Agabani; Osamu Minami; Jill Bormann; Bernard Le Foll; Leah Lobo; Ahmed N. Hassan (BMC, 2024)
Abstract Background There is a need for expanded options for therapeutic interventions for patients with posttraumatic stress disorder (PTSD) and substance use disorder (SUD). The study aimed to examine evidence for the feasibility, safety, and acceptability of a virtual Mantram Repetition Program for adults with PTSD and SUD. Methods This project utilized mixed-method design (explanatory sequential design) to collect quantitative and qualitative data to evaluate the program in terms of its feasibility and acceptability. The program took place over Webex, an encrypted virtual platform. The group ran over 8 weeks, was 90 min in length, and facilitated by two individuals per cohort. Each group had 4-5 participants given each group cycle. The study used the Mantram Repetition Program which is a brief mindfulness based non-tramua focused group intervention. Results Out of 43 participants enrolled, 5 people (11.6%) did not commence the program and 8 (18.6%) participants dropped out after commencing the program, resulting in 35 completers (81.4% retention rate). Treatment completion and retention were above 70%. Qualitative data explained several aspects of the program's acceptability including delivery methods, informative material provided and gaining a practical mindful tool to manage symptoms. Conclusions This study showed quantitative and qualitative evidence of the Mantram Repetition Program's feasibility, acceptability and safety to be used with individuals with PTSD-SUD. Although further evaluation of virtual Mantram Program to control group in longitudinal trials is needed to identify how it compares with other interventions in the field. Clinical trial registration number NCT05058963, (28/09/2021).